Mind games : 31 days to rediscover your brain - Cohen, Martin, 1964- (Malden, MA : Wiley-Blackwell, 2010)
This original and innovative book is an exploration of one of the key mysteries of the mind, the question of consciousness. Conducted through a one month course of both practical and entertaining 'thought experiments', these stimulating mind-games are used as a vehicle for investigating the complexities of the way the mind works.: By turns, fun, eye-opening and intriguing approach to thinking about thinking, which contains inventive and engaging 'thought experiments' for the general reader; Includes specially drawn illustrations by the French avant-garde artist, Judit; Reunites the social scie.
MIND GAMES; Contents; Forward!; Acknowledgements; How To Use This Book; Week 1: Influencing the Reptile Mind; Week 2: Observing the Development of Little Minds; Week 3: Experiments in Practical Philosophy; Week 4: Miscellaneous Philosophical Investigations; Debriefing; Appendix A: Three Lines Test; Sources and Suggestions for Further Reading; Index.
Includes bibliographical references and index.
Print version record.
Keywords: Consciousness; Thought experiments; Philosophy; PHILOSOPHY -- Mind & Body; Consciousness; Thought experiments; Electronic books